El experimento de Michelson y Morley: una propuesta didáctica para la enseñanza de la relatividad especial - Díaz López, Adriana Carolina (Revista Científica, 2011)
This document of a historical-critical method, shows a study of the Michelson-Morley experiment (1881-1887) by reading the original papers and college physics texts, from which we have characterized the problems embedded in the context nineteenth century that supported their implementation, the baseline scenario, building components and their respective conclusions. We propose some reflections on the interpretations that have text books, their contribution to late nineteenth century the concept of frame of reference with the idea of ether, and finally, the criteria of an educational proposal for a course inspecial relativity, emphasizing the use of history in the contexts of physics education.